Perancangan bilah tipe taperless pada kincir angin: Studi kasus di PT. Lentera Bumi Nusantara Tasikmalaya - N.H. Sari; W.G. Laksamana (Universitas Mataram, 2019)
The studies related to new renewable energy are still being developed. This study aims to design taperless blades on wind turbines, case studies at PT. Lentera Bumi Nusantara. The wind speed conditions in Tasikmalaya which are considered relatively moderate can be designed efficiently by the appropriate wind characteristics in Tasikmalaya. Microsoft Excel, Qblade, Solid Works, and aerodynamic equations have been used to design a blade. The result shows that the blades have a solid, easy to make and affordable structure that can produce mechanical power at low wind speeds with a radius, diameter hub and chord length of 0.8 m, 0.19 m and 0.12 m, respectively. A twisting angle at the base and at the end of the blade are 11.14° and 7.17°. respectively. The conclusion of this design exhibited that the blade design with the same edge blade can be applied to moderate wind speeds to produce efficient, compact and affordable wind turbines with wind characteristics in Tasikmalaya, Indonesia.